Strobilurins as growth-promoting compounds: how Stroby regulates Arabidopsis leaf growth - Van Dingenen, Judith; Antoniou, Chrystalla; Filippou, Panagiota S.; Pollier, Jacob; Gonzalez, Nathalie; Dhondt, Stijn; Goossens, Alain; Fotopoulos, Vasileios; Inzé, Dirk (My University, 2017)
Strobilurins are an important class of agrochemical fungicides used throughout the world on a wide variety of crops as protection against fungal pathogens. In addition to this protective role, they are reported to also positively influence plant physiology. In this study, we analysed the effect of Stroby (R) WG, a commercially available fungicide consisting of 50% (w/w) kresoxim-methyl (KM) as active strobilurin compound, on Arabidopsis leaf growth. Treatment of seedlings with Stroby resulted in larger leaves due to an increase in cell number. Transcriptome analysis of Stroby-treated rosettes demonstrated an increased expression of genes involved in redox homeostasis, iron metabolism and sugar transport. Stroby treatment strongly induced the expression of the subgroup Ib basic helix-loop-helix (bHLH) transcription factors, which have a role in iron homeostasis under iron-limiting conditions. Single loss-of-function mutants of three bHLHs and their triple bhlh039, bhlh100 and bhlh101 mutant did not respond to Stroby treatment. Although iron and sucrose content was not affected, nitric oxide (NO) levels and nitrate reductase (NR) activity were significantly increased in Stroby-treated rosettes as compared with control plants. In conclusion, we suggest that the Stroby-mediated effects on growth depend on the increased expression of the subgroup Ib bHLHs and higher NO levels.
Keywords: Subgroup Ib bHLH transcription factor; Strobilurins; Nitric oxide; Leaf growth